Intelligent adaptive edge systems：exploration and open issues - Xu WANG; Nanxi CHEN; Roujia ZHANG (物联网学报)
Edge intelligence has emerged as a promising trend of the new generation of Internet of things.Edge computing devices are widely distributed, with various diverse end devices and services, delay sensitive, and serve mobile terminals.Therefore, the edge system needs to provide flexible, diverse, reconfigurable and scalable services.From the application fields of adaptive edge computing, the application requirements of intelligent adaptive edge systems were explored, the existing adaptive edge systems and their basic framework were analyzed and summarized, and the application of artificial intelligence technologies was discussed, such as deep learning and reinforcement learning.Then, how to design a special intelligent algorithm in specific application fields was introduced.Finally, the research status and future challenges in this field were discussed.